Achieving Maqāṣid al-Sharīʿah through Artificial Intelligence: Mechanisms of Facilitation, Control, and Quality Assurance - Maiga, Mohamed Hamadikinane (Universitas Islam Negeri Alauddin Makassar, 2025)
This study examines how artificial intelligence (AI) can be applied to fulfill the objectives of Sharia (maqāṣid al-sharīʿah), especially in terms of facilitation, supervision, and quality assurance in addressing modern societal issues. Using a descriptive-analytical approach, the research focuses on defining AI and its significance, analyzing its characteristics in relation to Sharia goals, and evaluating the impact of its appropriate use. The study draws on a range of scholarly and scientific sources to assess how AI aligns with Islamic legal principles. The results indicate that AI possesses key strengths—such as speed, accuracy, and efficiency—that support the Sharia principle of taysīr (ease and facilitation). When used correctly, AI enhances societal well-being by improving control systems, increasing productivity in fields like agriculture and industry, and helping to reduce insecurity and scarcity. These benefits show that AI can be a powerful tool in achieving public interest and preventing harm, aligning with the ethical aims of Islamic law. This research stands out by directly linking the practical applications of AI to the values embedded in maqāṣid al-sharīʿah, offering an innovative perspective that bridges Islamic jurisprudence with emerging technologies. It also provides useful insights for policymakers, academics, and practitioners, suggesting that AI can be harnessed as an effective strategy for promoting ethical development in social, economic, political, and cultural spheres. The study encourages further exploration into models of ethical governance rooted in Islamic principles in the digital age.